Impact of Long-Term Annealing on Photoluminescence from Ge1−xSnx Alloys - Oluwatobi Olorunsola; Hryhorii Stanchu; Solomon Ojo; Krishna Pandey; Abdulla Said; Joe Margetis; John Tolle; Andrian Kuchuk; Yuriy I. Mazur; Gregory Salamo; Shui-Qing Yu (Crystals, 2021)
We report on the connection between strain, composition, defect density and the photoluminescence observed before and after annealing at 300 °C for GeSn samples with Sn content of 8% to 10%. Results show how the composition and level of strain influenced the separation between the indirect and direct optical transitions, while changes in the level of strain also influenced the density of misfit dislocations and surface roughness. The effect of annealing is observed to lower the level of strain, decreasing the energy separation between the indirect and direct optical transitions, while also simultaneously increasing the density of misfit/threading dislocations and surface roughness. The reduction in energy separation leads to an increase of photoluminescence (PL) emission, while the increase of misfit/threading dislocations density and surface roughness results in a decrease of PL. Consequently, the competition between these factors is observed to determine the impact of annealing on the PL. As a result, annealing increases the collected PL for small (≤40 meV) separation between the indirect to direct optical transitions in the as-grown sample while decreases the PL for larger (≥60 meV) separations. More generally, these numbers have a small dependence on the level of strain in the as-grown samples.